Building Practical Political Enlightenment in the Perspective of Local Wisdom - Rahmatulloh, Aang; Upa, Fatmawati Pua; Purwanto, Purwanto; Dahlan, Charly; Inayatullah, Muhamad Iqbal (Universitas Pahlawan Tuanku Tambusai, 2025)
According to the Big Indonesian Dictionary (KBBI) and Wikipedia, politics (from the Greek politikos, meaning “of, for, or relating to citizens”) is the process of forming and distributing power in society, including decision-making, particularly within the state, and represents an effort to combine various definitions known in political science as the art and science of achieving power through constitutional and non-constitutional means. Politics can be viewed from different perspectives: as citizens’ efforts to realize the common good (Aristotle’s classical theory), as the administration of government and the state, as activities aimed at gaining and maintaining power in society, and as the process of formulating and implementing public policy, all of which require understanding key elements such as political power, legitimacy, political systems, political behavior, participation, processes, and the dynamics of political parties; meanwhile, Hans J. Morgenthau in Politics Among Nations defines politics as a struggle for power. Local wisdom, according to the KBBI, is the maturity of society at the local community level, reflected in attitudes, behaviors, and perspectives that support the development of local potential and resources (both material and non-material) as a force for realizing positive change and contributing to national strength for a more advanced and modern nation based on the ideology of Pancasila and the 1945 Constitution.